Wanprestasi dalam Perjanjian Sewa Menyewa Properti Komersial Berdasarkan KUHPerdata dan Kompilasi Hukum Ekonomi Syariah - Wirakusuma, Anggi; Hasibuan, Amanda Syafani Al Ikhsan; Wijaya, Adhitya Aldhani; Azhar, Muhammad Yasir; Munthe, Muhammad Asdon (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research analyzes defaults in commercial property rental agreements based on the Civil Code (KUHPerdata) and the Compilation of Sharia Economic Law (KHES). The method used is normative juridical with a regulatory approach and case studies. The research results show that in the Civil Code, default includes not carrying out achievements, carrying out inappropriate achievements, or being late. In KHES, default is seen from the ijarah contract with the principles of justice and honesty. This research found a gap between legal theory and practice in the field, so that legal harmonization and increased legal understanding of the parties are needed.